The Role of ESG Factors in Shaping Financial Performance: Insights from Malaysia’s Industrial Landscape - Afani, Moh.; Abdani, Fadlil; Hafizi, Muhammad Riza (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2025)
Purpose: This study aims to analyze the effect of ESG on the financial performance of energy and materials sector companies listed on Bursa Malaysia from 2021 - 2023. Method: This research uses a quantitative approach with a purposive sampling technique, and 23 companies were obtained as samples. Data was obtained from Refinitiv Eikon and financial statements, and SPSS 30.0 was used. To analyze the data. Companies that did not have complete ESG data from 2021-2023 were excluded from the analysis. Results: The results of this study show that environmental performance has a significant negative effect on financial performance, social performance has no significant direct effect on financial performance, while governance has a significant positive impact on financial performance. Implications: This study provides strategic recommendations for companies, investors, and regulators in managing sustainability issues to support sustainable long-term value creation. Novelty: This study focuses on energy and basic materials companies listed on Bursa Malaysia, an emerging market that is still relatively rare in the ESG literature. Meanwhile, most of the previous studies focused on developed countries that have stricter ESG regulations and more mature sustainability implementation.